The Recognition of Pasifika Decolonial Pedagogies as Inclusive Practice in Law Schools and Critical Legal Scholarship - Fa’amatuainu, Bridget (Routledge, 2023)
In this chapter, I examine some of the key challenges and successes in critical pedagogical praxis from the active inclusion of Pasifika pedagogies in decolonial legal pedagogy, rarely reflected in the teaching pedagogies adopted across the six law schools of Aotearoa (New Zealand). I build on the collective experience of Pasifika Early Career Academics (PECA) engaged in both legal and non-legal academic disciplines (Fa’amatuainu 2023; Leenen-Young et al. 2021). On this view, I adopt the Cartography of Decolonization (Andreotti et al. 2015) as the “conceptual framework of analysis” to evaluate the three reform spaces (soft reform, radical reform, and beyond reform) through which I have enacted Pasifika decolonial pedagogies in law teaching. Accordingly, I argue that there is a need for more decolonial approaches adopted in legal education and the timely recognition of Pasifika epistemologies and Pasifika legal academics in critical legal scholarship, teaching and instruction of the law.